LINGUISTIC-BASED APPROACHES IN EFL CLASSROOMS: A SYSTEMATIC LITERATURE REVIEW OF THEIR IMPACT ON STUDENTS’ VOCABULARY AND SENTENCE STRUCTURE MASTERY - Jasman, Yulia Oktafia; Triana, Devi; Syahmiarni; Kardena, Absharini; Lismay, Leli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This systematic review synthesizes empirical and theoretical studies on linguistic-based techniques in EFL classes, particularly the effect of the approaches on students' mastery of vocabulary and sentence structure. This study considers 50 highly significant works published in the period 1991-2026 and addresses corpuses-based and data driven learning (DDL) methodologies, sentence combining instruction, frame semantic and integrated syntax-semantics-pragmatics approaches. It has been regularly demonstrated that corpuses-based DDL promote vocabulary retention, lexical diversity, collocational competencies and learner autonomy. Sentence combining and scaffolded writing frames enhance syntactic complexity and grammatical precision, but excessive dependence on frames could limit linguistic originality. The integration of teaching of syntax, semantics and pragmatics leads to better communicative competence than the teaching of grammar in isolation, although there are practical problems relating to the readiness of the teacher and the curriculum. Linguistic tools are generally well received by the learners, although the effects are contingent on the learner's competence levels and motivation. The review indicates some key gaps in research such as the lack of longitudinal data, insufficient attention to individual learners’ characteristics, and the continuing theory-practices divided in EFL instruction. This article discusses implications for curriculum design, teacher training and future research areas.